The antigenicity of silk-based biomaterials: sources, influential factors and applications. Issue 40 (20th September 2021) - Long, Yanlin; Cheng, Xian; Tang, Qingming; Chen, Lili
Abstract : This review focuses on the antigenicity of silk-based materials applied in biomedical applications. It summarizes the immunomodulatory applications of silk, including bone regeneration, vascularization, and protection from inflammation. Abstract : Silk is an ancient material with essential roles in numerous biomedical applications, such as tissue regeneration and drug delivery, because of its excellent tunable mechanical properties and diverse physical structures. In addition to the necessary functionalities for biomedical applications, another critical factor for materials applied in biology is the appropriate immune interactions with the body. This review focuses on the immune responses of silk-based materials applied in biomedical applications, specifically antigenicity. The factors affecting the antigenicity of silk-based materials are complicated and are related to the composition and structural characteristics of the materials. At the same time, the composition of silk-based materials varies with its species sources, such as silkworms, spiders, honey bees, or engineered recombinant silk. Additionally, different processing methods are used to fabricate different material formats, such as films, hydrogels, scaffolds, particles, and fibers, resulting in different structural characteristics. Furthermore, the resulting body reactions are also different with different degrees of the immune response. Silk protein typically induces a mild immune response, and immunogenicity can play active roles in osteogenesis, angiogenesis, and protection from inflammation. However, there are some rare reports of severe immune responses caused by silk, which can result in an allergic response or tissue necrosis. The source of allergenicity in silk-based materials is currently under-studied and how to regulate and eliminate the overreaction of the immune system is essential for further applications. Overall, the diverse characteristics of silk-based materials mostly show beneficial bioresponses with mild immunogenicity, and the tunable properties make it applicable in immune-related biomedical applications.